2020
DOI: 10.3390/cancers12030541
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Keratinocyte Skin Tumors Links Staphylococcus aureus Overabundance and Increased Human β-Defensin-2 Expression to Growth Promotion of Squamous Cell Carcinoma

Abstract: The skin microbiota plays a prominent role in health and disease; however, its contribution to skin tumorigenesis is not well understood. We comparatively assessed the microbial community compositions from excision specimens of the main human non-melanoma skin cancers, actinic keratosis (AK), squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). Keratinocyte skin tumors are characterized by significantly different microbial community compositions, wherein AK and SCC are more similar to each other than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 94 publications
(115 reference statements)
5
71
0
15
Order By: Relevance
“…Madhusudhan et al demonstrated that the microscopic score of bacterial structures was higher in iSCC and AK than in BCC and normal skin samples. 3 Similarly, Wood et al showed that S. aureus, one of the predominant pathogens causing SSI, was relatively abundant in AK and iSCC lesions than in the patients' non-lesional skin. 4 Although the precise mechanism remains unclear, the presence of abundant bacteria in invasive and in situ SCC lesions might have contributed to the high incidence of SSI observed in our study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Madhusudhan et al demonstrated that the microscopic score of bacterial structures was higher in iSCC and AK than in BCC and normal skin samples. 3 Similarly, Wood et al showed that S. aureus, one of the predominant pathogens causing SSI, was relatively abundant in AK and iSCC lesions than in the patients' non-lesional skin. 4 Although the precise mechanism remains unclear, the presence of abundant bacteria in invasive and in situ SCC lesions might have contributed to the high incidence of SSI observed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Madhusudhan et al demonstrated that the microscopic score of bacterial structures was higher in iSCC and AK than in BCC and normal skin samples 3 . Similarly, Wood et al showed that S. aureus , one of the predominant pathogens causing SSI, was relatively abundant in AK and iSCC lesions than in the patients’ non‐lesional skin 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, in skin cancers accompanied by significant changes in the composition of the bacterial communities present on the skin, the microbiome may be associated with the proliferation of tumor cells. In biopsies from patients with a keratinocyte skin tumor, overabundance of Staphylococcus aureus was associated with overexpression of hBD-2 and, importantly, with increased tumor proliferation [ 116 ]. It can be presumed that the overproduction of defensins has an indirect influence on the progression of neoplastic processes.…”
Section: Hbd-2 In Skin and Woundsmentioning
confidence: 99%
“…Recent studies demonstrate correlations between a particular composition of microbiome and a broad spectrum of diseases, including lung cancer, obesity, and even breast cancer (59,60). Microbiome-related pathways were also enriched in both AK and cSCC, especially the human papilloma virus (HPV), which has been shown to be positively correlated with keratinocyte cell proliferation, inflammation, and the immune response (34,61), suggesting that HPV is closely related to the occurrence of AK and cSCC and the transformation of AK to cSCC (62)(63)(64). In addition, a group of EMT-and autophagy-related genes involved in cSCC was identified, and most of the DEGs related to autophagy were downregulated.…”
Section: Discussionmentioning
confidence: 99%